Emotional burnout of Ukrainian teachers in the context of a full-scale invasion - Vadim Tkachenko; Yurii Prysiazhniuk; Olha Verkhovenko; Yuliia Nenko (Universidade Federal do Norte do Tocantins, 2024)
Teaching is considered an emotionally challenging profession that can lead to the emotional burnout of an employee. Factors that might be considered significant predictors of emotional burnout have been generalized. The following are suggested to be among the primary groups of symptoms of a teacher's emotional burnout: physical, socio-psychological, emotional, behavioral, and intellectual. The purpose of the study was to determine the manifestation of emotional burnout among university educators in the post-pandemic era under martial law and to find out the cause-and-effect relationship. A voluntary survey of 177 educators at four universities located in the central part of Ukraine, at a distance of more than 200 km from the line of direct military operations, was carried out. Boyko's "Diagnostics of the Level of Emotional Burnout" and the authors' questionnaire have been implied. The study revealed that 13% of educators have developed the syndrome of emotional burnout, and the syndrome is in the creation stage in 34.46%. In the structure of the syndrome of emotional burnout, the dominant phase is resistance. The exhaustion and stress phases are less pronounced. Among the dominant symptoms of emotional burnout are inadequate selective emotional responsiveness and a reduction in professional duties.